How is China countering “decoupling” from the Western world? An analysis of China’s “Anti-Decoupling” Strategies - Wu, Zehui (Université d'Ottawa | University of Ottawa, 2024)
This major research paper (MRP) examines China's strategic responses to the evolving concept of "decoupling" in its relations with the United States and the European Union, particularly in the aftermath of the COVID-19 pandemic. Historically, the US's China policy transitioned from a policy of economic integration, known as “engagement”, to a Cold-War-Style “containment”, reflecting the threat to the US’s hegemony brought by the rise of China, a failure of democratization in China and a perceived increase in China's aggressive posturing under Xi Jinping's leadership. While also re-evaluating its strategy, the EU labelled China a "systemic rival," highlighting a cautious approach to economic interdependence after Russia’s invasion of Ukraine. China's response to these shifts has been multifaceted. Firstly, Beijing adopted the Dual Circulation strategy, emphasizing a "controlled" market economy through significant investments in security and technology, which aims at mitigating external risks and reducing dependency on Western economic inputs. Secondly, Beijing is utilizing “securitization” to enhance control of the private section and foreign investments to reduce reliance on the West. Thirdly, while trying to divide the US and EU, China also introduced a series of measures to reduce its reliance on Western financial services. However, China’s ambiguous responses didn’t work as anticipated, forcing China to slow down the de-coupling process towards a New Cold War. Meanwhile, two major variables, Taiwan and Ukraine, might contribute to this fragile equilibrium, re-accelerating or even reaching the New Cold War, which is the end of the de-coupling process.